Characterising the viral aetiology of undiagnosed acute febrile illness in Uganda - Byaruhanga, Timothy (2023)
Acute febrile illnesses (AFI) are a significant cause of morbidity in Uganda and sub-Saharan Africa (SSA). The epidemiology and burden of disease due to viral AFI are unknown in Uganda despite an active surveillance system at the Uganda Virus Research Institute (UVRI). This work describes the epidemiology of arboviruses and other AFI from data and samples stored (from 2016 to 2019) at the UVRI, providing a candid picture of the spatiotemporal distribution and seasonality of arboviruses in Uganda. Furthermore, for the arbovirus-negative specimens stored at the UVRI, a virus discovery approach was applied using the widely affordable conventional Polymerase Chain Reaction (PCR) method and later augmented by high throughput sequencing (HTS). We identified the age group 5-14 (years) most at risk of arboviral infections. Generally, arboviruses were more prevalent during the first rainy season from March to May, with yellow fever virus (YFV) as the most prevalent arbovirus. A significant spatiotemporal cluster was observed in the central region, where most arbovirus activities occurred. Among AFI, conventional PCR detected enteroviruses (Coxsackie A4, B1 viruses and human echovirus E4), measles virus (MeV) genotype B3 and West Nile virus (WNV) lineage two. The MeV was phylogenetically analysed and determined to be different from previously circulating B3 strains in Uganda but identical to strains in neighbouring Kenya and Rwanda. Furthermore, the WNV, although similar to the ancestral 1937 strain, had acquired a motif (NYSTQ) in the envelope protein similar to that found in lineage one WNV strains. In addition, HTS discovered viruses undetected by PCR, such as Hepatitis C virus, Pegiviruses, and sequences belonging to Orbiviruses. The ever-decreasing costs of sequencing will support the application of PCR augmented by regular HTS in the surveillance of AFI and, thus, capture emerging and re-emerging viruses.